Repeated Peripheral Embolisms associated with Chronic Aortic Dissection - Aoyagi, Shigeaki; Amako, Mau; Wada, Kumiko; Kosuga, Tomokazu; Yasunaga, Hiroshi (International Journal of Angiology, 2019)
A male patient developed acute type B aortic dissection (AD) extending to the right external iliac artery (EIA) and left common femoral artery at the age of 56 years. Two months after the diagnosis of AD, he developed right renal infarction suggesting embolism, as the right renal artery arose from a false lumen containing a mural thrombus. Seven years later, at the age of 63 years, the patient was readmitted for acute onset of intermittent claudication in the right leg. On admission, arterial pulses distal to the right femoral artery were absent. The right ankle-brachial pressure index (ABI) was 0.66, while the left ABI was 1.06. Computed tomography (CT) confirmed chronic type B AD and revealed a localized occlusion of the right EIA and disappearance of a small protruding thrombus in the false lumen that was found on the previous CT, suggesting a second embolism. Since recovery of antegrade blood flow was insufficient after catheter embolectomy, femorofemoral bypass was performed with resolution of ischemic symptoms. Postoperatively, the ABI recovered to 0.99 in the right and 1.12 in the left, and CT showed a patent bypass graft and restoration of blood flow to the right leg. This case indicates that embolism should be recognized as one of the possible causes of acute organ ischemia in patients with AD, even in patients with chronic AD.
Keywords: aortic dissection; fragmentation of a mural thrombus; ischemic complication; limb ischemia; peripheral vascular embolism; renal embolism; type B aortic dissection